Republic of Fiji : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Fiji. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2017 Article IV Consultation highlights that Fiji's economy is recovering well after Tropical Cyclone Winston and is expected to record its eighth consecutive year of expansion in 2017. Growth is expected to pick up to about 4 percent in 2017, underpinned by reconstruction activities, a vibrant tourism sector, and the recovery of agriculture production. The growth momentum is projected to continue in the coming years. Inflation declined sharply in recent months as the supply of food items started to normalize and is projected to remain about 3 percent. Risks to the economic outlook are largely related to external developments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet